2011
DOI: 10.1038/emboj.2011.459
|View full text |Cite
|
Sign up to set email alerts
|

Human long non-coding RNAs promote pluripotency and neuronal differentiation by association with chromatin modifiers and transcription factors

Abstract: Long non-coding RNAs (lncRNAs) are a numerous class of newly discovered genes in the human genome, which have been proposed to be key regulators of biological processes, including stem cell pluripotency and neurogenesis. However, at present very little functional characterization of lncRNAs in human differentiation has been carried out. In the present study, we address this using human embryonic stem cells (hESCs) as a paradigm for pluripotency and neuronal differentiation. With a newly developed method, hESCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
489
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(500 citation statements)
references
References 45 publications
8
489
0
3
Order By: Relevance
“…However, little is known about their functional involvement in human neural differentiation [37,42]. We also examined the expression patterns of SOX2OT and its two novel variants during the course of neural differentiation of NT2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about their functional involvement in human neural differentiation [37,42]. We also examined the expression patterns of SOX2OT and its two novel variants during the course of neural differentiation of NT2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, expression patterns of several lncRNAs correlate with those of pluripotency regulators such as OCT4, Nanog, and SOX2 [37,38]. SOX2 is an intronless gene that lies within the third intron of another gene known as SOX2OT [28].…”
Section: Discussionmentioning
confidence: 99%
“…29 We found that this transcript was almost undetectable both in undifferentiated and in RA-treated BE(2)-C cells (Fig. 2SC).…”
Section: Resultsmentioning
confidence: 78%
“…Ng et al [41] screened the expression of lncRNAs before and after induction of human ESC differentiation into dopaminergic neurons and found that lncRNA_N1, _N2 and _N3 were weakly but significantly expressed after induction of neuronal differentiation. lncRNA_N1 and lncRNA_N3 might function as scaffolds for the interaction with transcription repressors, repressor element 1 (RE1; also called NRSE) silencing TF (REST; also called NRSF) and a PRC2 protein, suppressor of zeste 12 homologue (SUZ12), respectively, resulting in inhibition of their suppressor activity [41].…”
Section: (A) Long Non-coding Rnasmentioning
confidence: 99%
“…lncRNA_N1 and lncRNA_N3 might function as scaffolds for the interaction with transcription repressors, repressor element 1 (RE1; also called NRSE) silencing TF (REST; also called NRSF) and a PRC2 protein, suppressor of zeste 12 homologue (SUZ12), respectively, resulting in inhibition of their suppressor activity [41]. On the other hand, small modulatory dsRNAs encoding the RE1 sequence were found in the nucleus, where they interacted with the REST complex to promote transcription of RE1-associated genes [42].…”
Section: (A) Long Non-coding Rnasmentioning
confidence: 99%